2009
DOI: 10.1186/1757-1146-2-32
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging for chronic plantar heel pain: a systematic review and meta‐analysis

Abstract: BackgroundChronic plantar heel pain (CPHP) is a generalised term used to describe a range of undifferentiated conditions affecting the plantar heel. Plantar fasciitis is reported as the most common cause and the terms are frequently used interchangeably in the literature. Diagnostic imaging has been used by many researchers and practitioners to investigate the involvement of specific anatomical structures in CPHP. These observations help to explain the underlying pathology of the disorder, and are of benefit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
136
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 57 publications
10
136
3
5
Order By: Relevance
“…However, we are confident that our conservative findings did not result from decreased ultrasound sensitivity, as we used a lower pulse-repetition frequency setting compared to that used by Walther et al 23 (781 versus 1102 Hz), which improved sensitivity to lowfrequency shift. 25 Consistent with the findings of a systematic review investigating diagnostic imaging for plantar fasciitis, 16 our findings show greater plantar fascia thickness in participants with plantar fasciitis compared to controls, and a strong association between plantar fascia thickness greater than 4.0 mm and heel pain. However, further exploration of our data revealed that 9 controls had plantar fascia thickness greater than 4.0 mm, and of these, 7 had a BMI of 30 kg/m 2 or greater.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, we are confident that our conservative findings did not result from decreased ultrasound sensitivity, as we used a lower pulse-repetition frequency setting compared to that used by Walther et al 23 (781 versus 1102 Hz), which improved sensitivity to lowfrequency shift. 25 Consistent with the findings of a systematic review investigating diagnostic imaging for plantar fasciitis, 16 our findings show greater plantar fascia thickness in participants with plantar fasciitis compared to controls, and a strong association between plantar fascia thickness greater than 4.0 mm and heel pain. However, further exploration of our data revealed that 9 controls had plantar fascia thickness greater than 4.0 mm, and of these, 7 had a BMI of 30 kg/m 2 or greater.…”
Section: Discussionsupporting
confidence: 89%
“…Plantar fasciitis was confirmed by ultrasound assessment and considered present when the plantar fascia was 4.0 mm or greater at the calcaneal origin. 16 Exclusion criteria for case participants included corticosteroid injection of the heel within the past 3 months, posterior heel pain, systemic inflammatory disease, diabetes, and a history of local surgery. Participants with bilateral heel pain had only the most severely affected foot scanned.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Provided the insonating beam is directed perpendicular to the fascia, it appears as a striated echogenic structure, tapering smoothly from proximal to distal. Within 10mm of its origin, the central portion measures 3-4mm in thickness [1] [4].…”
Section: Anatomymentioning
confidence: 99%